Prevalence, diagnostic utility, and clinical characteristics of ZnT8 antibody in children with type 1 diabetes in Northern Taiwan - Ya-Ting Su; Yi-Hsuan Chou; Chiao-Fan Chiu; Yen-Chun Huang; Fu-Sung Lo (Pediatrics and Neonatology)
Background: The ZnT8 autoantibody is used to independently diagnose type 1 diabetes (T1D) and as a prediction factor in high-risk populations. This is the first report in Taiwan on the prevalence, diagnostic utility, and clinical characteristics of zinc transporter 8 autoantibody (ZnT8A) in children with T1D. Methods: We performed a retrospective analysis of 268 children (130 boys, 138 girls) newly diagnosed with T1D at three hospitals in North Taiwan from February 1994 to August 2021. Results: ZnT8A was detected in 117 patients (43.7 %). The combined diagnostic rate of the four antibodies, including glutamic acid decarboxylase autoantibody (GADA), islet antigen 2 autoantibody (IA2A), insulin autoantibody (IAA), and ZnT8A, can reach 86.19 % while that of the original three antibodies is 84.3 %. IA2A (64.9 %) showed the highest positive rate, followed by GADA (64.2 %), ZnT8A (43.7 %), and IAA (22.0 %). Of the 268 patients, five (1.9 %) were only ZnT8A+. All antibodies were positive in 19 (7.1 %) people, whereas 37 others (13.8 %) had all antibodies negative. ZnT8A has the strongest relationship with IA2A. 5 patients had ZnT8A positive only. 5/(37 + 5) (about 12 %) T1D patients were diagnosed by ZnT8A testing. Conclusions: ZnT8A testing can diagnose up to 12 % more patients with T1D along with three other antibodies. Furthermore, since the ZnT8A titer decreased over time, it should be tested within six months of onset in Taiwanese patients with T1D.